2005
DOI: 10.1128/mcb.25.14.5846-5858.2005
|View full text |Cite
|
Sign up to set email alerts
|

GDF11 Forms a Bone Morphogenetic Protein 1-Activated Latent Complex That Can Modulate Nerve Growth Factor-Induced Differentiation of PC12 Cells

Abstract: All transforming growth factor ␤ (TGF-␤) superfamily members are synthesized as precursors with prodomain sequences that are proteolytically removed by subtilisin-like proprotein convertases (SPCs). For most superfamily members, this is believed sufficient for activation. Exceptions are TGF-␤s 1 to 3 and growth differentiation factor 8 (GDF8), also known as myostatin, which form noncovalent, latent complexes with their SPC-cleaved prodomains. Sequence similarities between TGF-␤s 1 to 3, myostatin, and superfam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
150
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(154 citation statements)
references
References 45 publications
(91 reference statements)
4
150
0
Order By: Relevance
“…Although such cleavage is sufficient for activating most TGFβ-like proteins (Hogan, 1996), prototypical family members TGFβ 1-3 remain noncovalently bound to their cleaved prodomains in latent complexes (Massague, 1998). More recently it has been demonstrated that GDF8 and 11, which share ~90% sequence identity in their mature regions (Gamer et al, 1999;Ge et al, 2005;Nakashima et al, 1999), are also noncovalently bound to their respective prodomains in latent complexes (Ge et al, 2005;Hill et al, 2002;Lee and McPherron, 2001;Wolfman et al, 2003) (Fig. 5B).…”
Section: Growth and Differentiation Factors 8 And 11 (Gdfs 8 And 11)mentioning
confidence: 99%
See 2 more Smart Citations
“…Although such cleavage is sufficient for activating most TGFβ-like proteins (Hogan, 1996), prototypical family members TGFβ 1-3 remain noncovalently bound to their cleaved prodomains in latent complexes (Massague, 1998). More recently it has been demonstrated that GDF8 and 11, which share ~90% sequence identity in their mature regions (Gamer et al, 1999;Ge et al, 2005;Nakashima et al, 1999), are also noncovalently bound to their respective prodomains in latent complexes (Ge et al, 2005;Hill et al, 2002;Lee and McPherron, 2001;Wolfman et al, 2003) (Fig. 5B).…”
Section: Growth and Differentiation Factors 8 And 11 (Gdfs 8 And 11)mentioning
confidence: 99%
“…GDF11 also appears to play roles in anterior-posterior patterning of the axial skeleton (McPherron et al, 1999). BMP1/TLD-like proteinases have been demonstrated to cleave within GDF8 and 11 prodomain sequences, thus liberating the mature proteins and enabling downstream signal transduction (Ge et al, 2005;Wolfman et al, 2003). Interestingly, recombinant GDF8 prodomain with a single amino acid substitution that renders it resistant to cleavage by BMP1/TLD-like proteinases is capable of inducing increased muscle mass when injected into normal adult mice, whereas wild type GDF8 prodomain has no effect (Wolfman et al, 2003).…”
Section: Growth and Differentiation Factors 8 And 11 (Gdfs 8 And 11)mentioning
confidence: 99%
See 1 more Smart Citation
“…8 BMP-1 may convert precursor proteins, including laminin-5, procollagen, growth and differentiation factors 8 and 11, and TGF-b1, into their active forms, which play manifold roles in cell adhesion and in regulating mineralization in the extracellular matrix of hard tissue. 8,[10][11][12][13][14][15][16][17] BMP-1 may also activate two other BMP family members, BMP-2 and BMP-4, by cleaving their antagonist, chordin. 11 Therefore, BMP-1 is believed to be an intermediate factor between the TGF-b and BMP signaling pathways.…”
mentioning
confidence: 99%
“…Mouse Gdf11 (21) and HA epitope-tagged human LTBP-2 and mouse LTBP-3 (13) were expressed using pcDNA3 vectors.…”
Section: Methodsmentioning
confidence: 99%